(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
We examined 100 children with chronic pneumonia, who were divided into two groups: Group I consisted of 30 patients aged 12-14 years (with bronchial deformation - 24 patients; with bronchiectasis - 6), Group II - 70 patients aged 15 - 15 years. 16 years (with bronchial deformation - 46 patients; with bronchiectasis - 24). An analysis of the indicators of the blood hemostasis system in patients with chronic pneumonia was carried out. The presented data emphasize the significant pathogenetic significance of changes in hemostasis in patients with chronic pneumonia, which requires the search for new methods of pathogenetic therapy based on anticoagulant effects.